Metode Dialog Interaktif sebagai Strategi Pembelajaran Al-Qur’an Hadits dalam Meningkatkan Kesadaran Akhlak: Studi Refleksi Hadits tentang Menjaga Diri dari Api Neraka - Ilma, Labibah Sayaka; Suyudi, M. (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
This study aims to analyze the implementation of the interactive dialogue method in Islamic education as a strategy to enhance students’ moral awareness. The focus is centered on the reflection and understanding of the hadith